2020
DOI: 10.20944/preprints202010.0402.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical Model for Blood Glucose Detection using Electrical Impedance Spectroscopy

Abstract: Pathogens and adulterants in human feeding consumables can be readily identified according to their electrical properties. Electrical bioimpedance analysis (BIA) has been widely used for body contents characterization, such as blood, urine, lactate and sweat. If the blood glucose concentration alters the electrical properties of the blood medium, then the impedance spectrum obtained by BIA can be used to measure glycemia. In some applications, artificial neural networks allows the correlation of these paramete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These devices emit radio waves through the skin to measure the molecular signature of glucose in the blood with spectroscopy (Park, 2021). Another promising approach uses electrical bioimpedance analysis (Pedro et al, 2020). Regardless of the technology, the Food and Drug Administration requires 95 percent of sensor values within 15 percent of blood glucose levels for approval as a medical device (Delbeck et al, 2019).…”
Section: Noninvasive Cgmmentioning
confidence: 99%
“…These devices emit radio waves through the skin to measure the molecular signature of glucose in the blood with spectroscopy (Park, 2021). Another promising approach uses electrical bioimpedance analysis (Pedro et al, 2020). Regardless of the technology, the Food and Drug Administration requires 95 percent of sensor values within 15 percent of blood glucose levels for approval as a medical device (Delbeck et al, 2019).…”
Section: Noninvasive Cgmmentioning
confidence: 99%
“…This sensing technology features compact size, low cost, fast response and high sensitivity. Previous studies have demonstrated its efficacy in many clinical applications such as venipuncture detection [20], cancer detection [21], stage monitoring in bone drilling [22] and glucose measurement [23].…”
Section: Introductionmentioning
confidence: 99%